2017
DOI: 10.1155/2017/4259704
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Randomised Controlled Trials of Therapies in Breast Cancer in Low and Middle Income Countries

Abstract: Objectives. The objectives of this study were to identify the randomised controlled trials in breast cancer occurring in low and middle income countries (LMICs) generally and within Sub-Saharan Africa specifically, to describe the current status and identify opportunities for further research in these areas. Materials and Methods. Data for this study were obtained from ClinicalTrials.gov. The search term “Breast Cancer Research” was used, and relevant information extracted and analysed. Results. 2414 trials we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…A 2016 study that reviewed registered breast cancer studies in LMICs found that, of the LMICs, Asia had the most trial registrations, with India as the leader in the region. 16 Similar to the current study, this previously published report demonstrated that few countries on the African continent had clinical trials registered for patients with any of the three cancer subtypes of interest.…”
Section: Discussionsupporting
confidence: 83%
“…A 2016 study that reviewed registered breast cancer studies in LMICs found that, of the LMICs, Asia had the most trial registrations, with India as the leader in the region. 16 Similar to the current study, this previously published report demonstrated that few countries on the African continent had clinical trials registered for patients with any of the three cancer subtypes of interest.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with previous studies, we found that the cancers evaluated in these trials do not reflect the disease burden in these health systems. 17 …”
Section: Discussionmentioning
confidence: 99%
“…There was a general alignment between the proportion of RCTs and deaths for lung, urologic, and brain cancers. 20) 77 (17) .18…”
Section: Design Characteristics Of Rctsmentioning
confidence: 99%
“…Moreover, protocols with systemic therapies are often unsuitable in SSAs given the scarcity of care facilities, drugs, and trained personnel. Therefore, the objectives of protocols and FBC healthcare strategies must be tailored to local settings 58 …”
Section: Discussionmentioning
confidence: 99%
“…The visits of obstetrician‐gynecologists are invaluable opportunities for early FBC detection or recurrence 58 given the limited availability and access to mammographic examinations. Also, the patient‐doctor communication skills of obstetrician‐gynecologists can help increase awareness, explore stigma and misconceptions related to the disease, 40 and provide FBC patients information about the balance between risks and benefits of surgeries.…”
Section: Discussionmentioning
confidence: 99%